Pengaruh Character, Capacity, Capital, Collateral, Condition Of Economy Melalui Kepercayaan Bank Terhadap Kualitas Kredit Pada Nasabah Bank Bri Unit Tanjungrejo Malang - Rika Wulandari; Jeni Susyanti; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This research aims to examine the Effect of Character, Capacity, Capital, Collateral, Condition of Economy through Bank Trust on Credit Quality to BRI Unit Tanjungrejo Malang Bank customers. The number of samples was determined using the Slovin formula and the results obtained were 97 respondents. The data were obtained by distributing questionnaires to BRI Unit Tanjungrejo Malang Bank customers who were selected by purposive sampling. Data analysis in this study used SPSS version 23. Data testing techniques used in this study included validity testing, reliability testing, normality testing, path analysis (path analysis), and research hypothesis testing. The results of this study indicate that Character, Capacity, Capital, Collateral and Condition of Economy partially have a direct effect on Bank Confidence. Character, Capacity, Capital, Collateral partially have a direct effect on Credit Quality. Meanwhile, the Condition of Economy has no direct effect on Credit Quality. Bank trust can mediate Character, Capacity, Capital, Collateral on Credit Quality. But bank trust cannot mediate the Condition of Economy on Credit Quality. Keywords: 5C, Bank Trust, Credit Quality